Ag/Fe3O4 bifunctional nanocomposite for SERS detection of non-steroidal anti-inflammation drug diclofenac - Bui, Duy Hai; Pham, Do Chung; Osial, Magdalena; Pisarek, Marcin; Tycova, Anna; Pham, Thi Nam; Nguyen, Thi Thanh Huong; Vu, Thi Thu; Nguyen, Thi Thanh Ngan (Vietnam Journal of Science and Technology, 2024)
In this work, a bifunctional nanocomposite based on silver and iron oxide nanoparticles (AgNPs/Fe3O4) was prepared and then used as SERS substrate (surface-enhanced Raman spectroscopy) for sensing diclofenac which is one of the most widely used non-steroid anti-inflammation drugs. AgNPs/Fe3O4 nanocomposite was synthesized by combining co-precipitation of iron oxide and in-situ reduction of silver nanoparticles. Morphology and structural studies revealed a conjugated structure in which silver nanoparticles (80 nm in diameter) were surrounded by iron oxide nanoparticles (18 nm in diameter). There is a slight blue-shift in position of plasmon peak from 405 nm for silver nanoparticles to 375 nm for AgNPs/Fe3O4 nanocomposite. Even the saturation magnetization (Ms) of the Ag/Fe3O4 nanocomposite only reached 28 emu.g-1 but still good enough for immobilizing nanocomposite structures onto the substrate. The use of AgNPs/Fe3O4 nanocomposite as SERS substrate for sensing application was demonstrated with using diclofenac as a model. The detection limit and enhancement factor of the SERS-based diclofenac sensor were found to be 10-12 M and 2.6×1010, respectively. Such kind of bifunctional nanocomposite will probably help us to avoid time-consuming process to immobilize metal nanoparticles onto the surface, and also allow us to regenerate the substrate for multiple uses.